2021
DOI: 10.2991/ahsr.k.210115.109
|View full text |Cite
|
Sign up to set email alerts
|

Mental Emotional Disorders in the Community

Abstract: According to Indonesia Basic Health Research 2018, the prevalence of mental emotional disorders which is indicated by depression and anxiety symptoms reached 9.8% of the total households in Indonesia. Screening of mental emotional disorders in a population at risk needs to be done. Therefore, people with mental emotional disorders can be handled promptly and appropriately. The purpose of this study was to determine the prevalence of mental emotional disorders in risk community through screening in the communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
(18 reference statements)
1
3
0
1
Order By: Relevance
“…This is different from research conducted by Puspitosari and Wardaningsih (2020), which showed a meaningful relationship (P <0.05). This study demonstrated that respondents with low levels of education tended to experience emotional and mental disorders [9]. Similar results were also obtained from research conducted by Manners et al ( 2016), which showed that education level is related to mental health; the higher a person's educational level, the higher level of education correlates with a higher level of mental disorders [14].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This is different from research conducted by Puspitosari and Wardaningsih (2020), which showed a meaningful relationship (P <0.05). This study demonstrated that respondents with low levels of education tended to experience emotional and mental disorders [9]. Similar results were also obtained from research conducted by Manners et al ( 2016), which showed that education level is related to mental health; the higher a person's educational level, the higher level of education correlates with a higher level of mental disorders [14].…”
Section: Discussionsupporting
confidence: 89%
“…This study had no statistically significant relationship between gender and psychopathology (P = 0.758). This is also by research conducted by Puspitosari and Wardaningsih (2020), which showed that there was no significant relationship between gender and psychopathology (P = > 0.05) [9]. This differed from research conducted by Tampubolon and Hanandita (2014), which showed that female respondents are 2-3 times more prone to depression than male respondents [10,11].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Gangguan Kesehatan jiwa merupakan permsalahan atau konflik umum yang bukan ada di negara Indonesia saja, namun menjadi permasalahan di seluruh dunia, yang sekarang semakin meningkat (Warih, 2020). Sedangkan menurut ulman dikenang untuk perilaku aneh jika bentuk tunggalnya menunjukkan perilaku khas, tidak mengikuti aturan yang ada, perilaku yang mengganggu dan tidak dapat dipahami menurut standar biasa dianggap tidak normal baik secara fisik maupun mental (Slamet, 2007)…”
Section: Pendahuluanunclassified
“…The incidence of hypertension in Indonesia from survey results in Asia, shows that hypertension sufferers reach 31.7% of the total adult population (Pratiwi et al, 2021) (Sudikno et al, 2023) (Indriawati & Syaifudin, 2020) (Hasanah, 2019). Hypertension continues to increase and can be seen from the incidence of hypertension in various provinces in Indonesia, namely 35.8% in the Special Region of Yogyakarta, 30.9% in Bangka Belitung, 30.8% in Kalimantan (Sitanggang et al, 2022) (Puspitosari & Wardaningsih, 2021) (Hulu et al, 2021). South, 29.4% in West Java.…”
Section: Introductionmentioning
confidence: 99%